The Effect of Work Climate Work Environment and Work Motivation on the Morale of Contract Employees at the Environmental Service of Gianyar Regency - Wirawan, I Kadek Arya Yudi; Adiandari, Ade Maharini; Geriadi, Made Ayu Desy (Universitas Mercu Buana, 2025)
The aim of this research is: To determine the influence of work climate, work environment and work motivation simultaneously and partially on work morale at the Gianyar Regency Environmental Service. Sampling was carried out using the census method or saturated sample, namely 48 contract employees. The data sources used are primary data and secondary data, the nature of the data is quantitative data and qualitative data. Data collection techniques include observation, interviews, questionnaires and documentation studies. The research results show that work climate, work environment and work motivation have a positive and significant effect simultaneously and partially on the work morale of contract employees at the Gianyar Regency Environmental Service.